Promoting Professional Identity Formation of Novice EFL Teachers in E-teaching Through Online Image Management (OIM) Strategies - راضیه فلاح; عزیزه چالاک; حسین حیدری تبریزی (Journal of Applied Linguistics)
Although the EFL teachers' challenges in developing and enhancing Professional Identity Formation (PIF) in face-to-face and virtual instruction contexts have extensively been explored, there were a limited set of practical and advantageous strategies, particularly for the novice teachers, in promoting their PIF in E-teaching especially since the emergence of changed priority of teaching contexts amid the COVID-19 outbreak. Accordingly, this study attempted to check the Iranian novice EFL teachers’ PIF, uncover the potential impacts of utilizing Online Image Management (OIM) strategies in promoting their PIF, and identify the most-preferred OIM strategies. Based on the convenience sampling, 184 male and female Iranian novice EFL teachers were selected to participate in this quasi-experimental study. Two instruments, including a Questionnaire of Perceived Professional Identity (QPPI) and a series of Quantitative Online Interviews (QOIs), were used to collect the data via the virtual platform of Survey Planet. The descriptive statistics and Independent Samples t-Test packages in R were utilized to analyze the data. The results confirmed the low levels of professional identity among Iranian novice EFL teachers, verified the significant effects of OIM strategies in promoting PIF of Iranian novice EFL teachers, and shed light on reflection practices and strategies in enhancing digital literacy as the most-favored OIM strategies in promoting PIF among these teachers. This study may provide implications for EFL teachers and trainers in helping novice EFL teachers to promote their PIF with OIM strategies.